Dihydropyrimidine Dehydrogenase Gene Variation and Its Association with 5-Fluorouracil Toxicity in Colorectal Patients - Salehifar, Ebrahim; Abd Haghighi, Mohammad Javad; Negarandeh, Reza; Janbabai, Ghasem; Safgafi, Fatemeh; Jalali, Hossein (Asian Pacific Journal of Cancer Biology, 2018)
Objective: Dihydropyrimidine dehydrogenase (DPD), an enzyme translated by DPD gene (DPYD), has a critical role in the metabolism of 5-fluorouracil (5FU). In this study we aimed to investigate the frequency of the IVS14+1 G>A, 2194G>A, 2846 A>T mutations in the DPYD gene in colorectal cancer patients in north of Iran and their association with side effects of 5FU. Methods: Venous blood samples of 89 colorectal cancer patients were drawn. After the DNA extraction from nuclear cells, a polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method was used to detect the frequency of the IVS14+1 G>A and 2846 A>T mutations. Tetra-Primer ARMS PCR optimization method was used to detect the 2194 G>A mutation. Side effects were classified according to CTCAE (common terminology criteria for adverse events V. 4) and the association between different polymorphisms and side effects were evaluated. Results: Of 89 colorectal patients, the frequency of IVS14+1 G>A and 2846 A>T polymorphism was 4 (5.1%) and 1 (1.1%), respectively. The 2194 G>A polymorphism was not detected. All 4 patients were heterozygous for IVS14+1 G>A mutation, whereas the only patient with 2846 A>T polymorphism was homozygous. Some adverse effects of 5FU including diarrhea, vomiting, mucositis and stomatitis were more frequent in patients with IVS14+1 G>A polymorphism. Conclusion: The prevalence of IVS14+1 G>A mutation in our patients were relatively high and was associated with a higher occurrence of 5FU-associated toxicities.